(untitled) (Global Journal of Medical Research, 2014)
As per World Health Organization estimates more than a billion people live with some form of disability worldwide. Disability casts a significant impact in the development of a disabled child and a constant struggle for the families as well. Multiple political, health care delivery system and social determinants have been identified which have limited the scope of benefit to disabled children. A disabled child represents a vulnerable section of the society because of the socio-psychological restrictions due to disability. The need is to have a comprehensive program for the welfare of the disabled child and their family members to enable them to lead a normal life. To conclude, for doing adequate justice to the differently-abled child, ample scope exists. Political commitment, multi-sectoral involvement and collaboration with international agencies are the main pillars for extending the benefit of welfare measures to the disabled child.